Quantum interference effects in a system of two tunnel point-contacts in the presence of single scatterer: simulation of a double-tip STM experiment - Khotkevych, N.V.; Kolesnichenko, Yu.A.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The conductance of systems containing two tunnel point-contacts and a single subsurface scatterer is investigated theoretically. The problem is solved in the approximation of s-wave scattering giving analytical expressions for the wave functions and for the conductance of the system. Conductance oscillations resulting from the interference of electron waves passing through different contacts and their interference with the waves scattered by the defect are analyzed. The prospect for determining the depth of the impurity below the metal surface by using the dependence of the conductance as a function of the distance between the contacts is discussed. It is shown that the application of an external magnetic field results in Aharonov–Bohm type oscillations in the conductance, the period of which allows detection of the depth of the defect in a double tip STM experiment.